Spatial and Temporal Analysis of Host Cells in Tracheal Graft Implantation. (10th June 2020) - Danielson, Alex; Liu, Lumei; Shontz, Kimberly M.; Syed, Hassan; Dharmadhikari, Sayali; Reynolds, Susan D.; Breuer, Christopher K.; Chiang, Tendy
Abstract : Objectives/Hypothesis: The ideal trachea replacement would be a living graft that is genetically identical to the host, avoiding the need for immunosuppression. We have developed a mouse model of syngeneic tracheal transplant that results in long‐term survival without graft stenosis or delayed healing. To understand how host cells contribute to tracheal transplant integration, we quantified the populations of host cells in the graft and native trachea following implant. Study Design: Tracheal transplant, tracheal replacement, regenerative medicine, animal model. Methods: Tracheal grafts were obtained from female C57BL/6 mice and orthotopically transplanted into syngeneic male recipients. Cohorts were euthanized on day 14, day 45, and day 90 post‐transplantation. Host and graft tracheas were explanted and analyzed by histology. Male host cells were quantified using fluorescence in situ hybridization, and macrophages were quantified with immunofluorescence. Results: Evidence of host‐derived cells was found in the midgraft at the earliest time point (14 days). Host‐derived cells transiently increased in the graft on day 45 and were predominantly found in the submucosa. By day 90, the population of host‐derived cells population declined to a similar level on day 14. Macrophage infiltration of host and graft tissue was observed at all time points and was greatest on day 90. Conclusions: Tracheal graft integration occurs by way of subacute transient host‐cell infiltration and is primarily inflammatory in nature. Host‐cell contribution to the graft epithelium is limited. These data indicate that creation of living, nonimmunogenic tracheal graft could serve as a viable solution for long‐segment tracheal defects. Level of Evidence: 3 Laryngoscope, 131:E340–E345, 2021